Potential Impacts of Lead on Health: A Review of Environmental Exposure, Population at Risk, and Toxic Effects - Simatupang, Meithyra Melviana; Veronika, Erna; Irfandi, Ahmad; Azteria, Veza (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Lead, a heavy metal, has been proven to influence the ecosystem negatively. The use of lead in processing or as raw materials increases Pb exposure to humans from various sources, including waste or consumed products. This study aims to determine the most recent information regarding lead contamination sourced from the environment, at-risk populations, and the health impacts of this heavy metal contamination. Results and Discussion: This systematic review used a database sourced from Google Scholar. The keywords searched were "lead exposure, environment, or health" in articles published in 2020-2023. After article screening and exclusion, 26 research articles were eventually reviewed. Lead was detected in water, air, and soil, generally in various foods or products consumed by humans. Environmental factors were the most frequent source of contamination. The population at risk of lead exposure were children. Several studies have found that various health impacts were significantly associated with lead exposure from different environmental sources and lead concentrations in biomarkers. Conclusion: Pb contamination was increasingly widespread in the environment through various sources. Exposure to lead may cause diverse health problems.